Estudio de prefactibilidad para la instalación de máquinas recolectoras de botellas de plástico PET en zonas estratégicas que premien a las personas a cambio de su depósito - Sanchez Santillan, Maria Alejandra (2023)
The purpose of this research project is to determine the market, technical, economic and social viability for the installation of PET plastic bottle collection machines in strategic areas that reward people in exchange for their deposit. First, the general aspects will be described as problems, objectives, scope and justifications for the topic. Also, in this chapter you will find the project hypothesis, the referential framework and the conceptual framework of the research. Likewise, the market study carried out will be explained, where it was obtained that the service will be aimed at people between 13 and 65 years old who belong to the NSE B, C and D who have recycling as a habit of life and who live in Metropolitan Lima. Also, the main factors to choose the best location for the reverse collection machines will be presented, which will be located in 30 bus stops of the different lines of the Lima corridor. On the other hand, it will be exposed that the installed capacity is limited by the technology size due to the kg of PET plastic that can be collected, where the capacity is 2 062 609,92 kg per year with only 30 machines. As for the economic evaluation, the investment amounts to S/ 3,272,185.08, with an economic NPV of 316 276,35 and a financial NPV of 596 835,53; 28% economic IRR and 36% financial IRR; With which it can be concluded that the project is economically and financially viable. Finally, it will be presented that the project has a positive social impact, since it generates an accumulated added value on the total investment of 4,20 and a capital density of 306 517,10.